Sosialisasi Pengembangan Produk Usaha Jahit Ibu Noni Di Kelurahan Lempuing Kecamatan, Ratu Agung Kota Bengkulu - Radilli, Putri; Afriani, Sulisti; Zoniarti, Zoniarti; Yustanti, Nirta Vera; Ariska, Yesi Indian (Universitas Dehasen Bengkulu, 2024)
This community service activity aims to optimize the management of making school clothes and pants in the Small and Medium Industry environment. The main focus of this program is to improve the efficiency of the production process and expand the reach of product marketing through technology and digital marketing strategies. The methods used are survey and observation, technical assistance and monitoring and evaluation. In the production aspect, the main challenge is that raw materials in the form of fabric are an important highlight for convection business people In addition to raw materials, the sewing process is also a challenge for convection entrepreneurs. Because the sewing process also affects the results of the product, for example from the neatness of the stitches, the ability of tailors to translate consumer wishes with the products produced. So convection entrepreneurs must really pay attention to the quality of the stitches of their products.